A perspective from the EU: unintended genetic changes in plants caused by NGT—their relevance for a comprehensive molecular characterisation and risk assessment - Koller, Franziska; Cieslak, Michael (Frontiers in Bioengineering and Biotechnology, 2023)
Several regions in the world are currently holding discussions in regard to the regulation of new genomic techniques (NGTs) and their application in agriculture. The European Commission, for instance, is proposing the introduction of specific regulation for NGT plants. Various questions need to be answered including e.g. the extent to which NGT-induced intended and unintended genetic modifications must be subjected to a mandatory risk assessment as part of an approval procedure. This review mostly focuses on findings in regard to unintended genetic changes that can be caused by the application of NGTs. More specifically, the review deals with the application of the nuclease CRISPR/Cas, which is currently the most important tool for developing NGT plants, and its potential to introduce double strand breaks (DSBs) at a targeted DNA sequence. For this purpose, we identified the differences in comparison to non-targeted mutagenesis methods used in conventional breeding. The review concludes that unintended genetic changes caused by NGT processes are relevant to risk assessment. Due to the technical characteristics of NGTs, the sites of the unintended changes, their genomic context and their frequency (in regard to specific sites) mean that the resulting gene combinations (intended or unintended) may be unlikely to occur with conventional methods. This, in turn, implies that the biological effects (phenotypes) can also be different and may cause risks to health and the environment. Therefore, we conclude that the assessment of intended as well as unintended genetic changes should be part of a mandatory comprehensive molecular characterisation and risk assessment of NGT plants that are meant for environmental releases or for market authorisation.